Variation Studies in Sandal (Santalum album L.): I. Time of Emergence and Seedling Vigour - Sindhu Veerendra, H. C.; Sarma, C. R. (Indian Forester, 1990)
The effect of time of emergence of seedlings on seedling vigour is studied in this paper. It is found that the sooner the emergence, the poorer will be the vigour and the later the emergence of seedlings, the greater will be the vigour of seedlings. Among the seed sources tried, the best one is identified through statistical analysis of the data recorded.